Disruptive Peers and Academic Performance: Short- and Long-Term Outcomes - Sofoklis Goulas; Silvia Griselda; Rigissa Megalokonomou; Yves Zenou (CESifo GmbH, 2024)
How do disruptive peers shape academic and career paths? We examine this question by leveraging the random assignment of students to classrooms in Greece and identifying the effects of peer disruptiveness on academic performance and career paths. Using suspension hours as a measure of disruptiveness, we find that students assigned to more disruptive classrooms have lower academic achievement, a higher risk of grade retention, and reduced likelihood of graduating from high school on time. They are also less likely to pursue competitive STEM fields or enroll in selective postsecondary programs. The adverse effects are more pronounced for students from low-income areas, in larger classrooms, or with fewer female peers. Using a lab-in-the-field experiment, we find that exposure to multiple disruptors, compared to just one, reduces students' study motivation, college aspirations, and readiness for science studies and careers, especially for those seated closer to disruptive peers.
Keywords: I24; I26; J16; J24; 330; disruption; suspension; random classroom assignment; high school graduation; STEM careers; lab-in-the-field experiment